2011
DOI: 10.2215/cjn.06630810
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Cumulative Access Survival in Arteriovenous Fistulas Requiring Interventions to Promote Maturation

Abstract: SummaryBackground and objectives New arteriovenous fistulas (AVF) are frequently unsuitable for hemodialysis because of AVF nonmaturation. Aggressive endovascular or surgical interventions are often undertaken to salvage nonmaturing AVFs. The effect of early interventions to promote AVF maturation on subsequent long-term AVF outcomes is unknown.Design, setting, participants, & measurements We evaluated 173 hemodialysis patients from two academic centers who received a new AVF. Of these, 96 (56%) required no fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
122
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(130 citation statements)
references
References 46 publications
5
122
3
Order By: Relevance
“…Studies have shown prolonged maturation times in patients with diabetes (31) and decreased primary and secondary patency (32). However, other studies have also shown no association between diabetes and time to maturation (33), risk of nonmaturation (34,35), or patency (36). Even in a well validated prediction model (37), no association between diabetes and risk of nonmaturation was found (27).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…Studies have shown prolonged maturation times in patients with diabetes (31) and decreased primary and secondary patency (32). However, other studies have also shown no association between diabetes and time to maturation (33), risk of nonmaturation (34,35), or patency (36). Even in a well validated prediction model (37), no association between diabetes and risk of nonmaturation was found (27).…”
Section: Comorbiditiesmentioning
confidence: 99%
“…A combination of female gender and increased age (> 65) has been shown to be significantly associated with non-maturation when compared to men of the same age group [22,24]. However, several other studies found no significant association between female gender and high risk of AVF non-maturation [22,25,27].…”
Section: Introductionmentioning
confidence: 99%
“…The rate of systemic fistula infections is more difficult to interpret because events rates were low and results were not reported as per 1000 fistula-days, with different reporting periods: 2003 to mid-2004 for RLC and 2004-2009 for BHC. In addition, interpretation of the rate of fistula loss and need for surgical intervention is hampered by the exclusion of radiologic interventions that represent the majority of interventions in patients with fistula and have been significantly associated with fistula patency outcomes (21). The utilizationrelated outcomes were as follows: Training time and ongoing support encounters were significantly higher with BHC (median, 46 days [interquartile range, 37-60 days] versus 37 days [interquartile range, 25-58 days] in the RLC and 1 encounter per 13.2 fistula-days versus 1 encounter per 19 fistula-days for RLC).…”
mentioning
confidence: 99%